Genetic diversity, population structure, and relationships of apricot (Prunus) based on restriction site-associated DNA sequencing. (1st May 2020) - Li, Wenwen; Liu, Liqiang; Wang, Yanan; Zhang, Qiuping; Fan, Guoquan; Zhang, Shikui; Wang, Yatong; Liao, Kang
Abstract: Single-nucleotide polymorphisms (SNPs) are the most abundant form of genomic polymorphisms and are widely used in population genetics research. Here, high-throughput sequencing was used to examine the genome-level diversity, population structure, and relationships of apricot, which are important for germplasm conservation and molecular breeding. Restriction site-associated DNA sequencing (RAD-seq) was adopted to sequence 168 Prunus spp. accessions distributed in five ecological groups, including 74 accessions of cultivated Prunus armeniaca L. and 94 accessions of wild apricots ( P. armeniaca L. and Prunus sibirica L.), which generated 417, 961 high-quality SNPs. We used cluster, genetic structure, and principal component analyses to examine the genetic diversities and genetic relationships of the 168 accessions. The Dzhungar-Ili ecological group accessions showed the highest genetic diversity in terms of private allele number, observed heterozygosity, and nucleotide diversity. We speculate that the Central Asian ecological group accessions were domesticated from the Dzhungar-Ili ecological group accessions. The population structure and gene flow of the North China and European ecological group accessions suggested a genetic background of P. sibirica . We argue that the two groups should be considered hybrid swarms connected to P. sibirica by continuous and extensive gene flow. P. armeniaca originated in Northwest China (Ili Valley), subsequently spread throughout Central Asia, and eventually spread to Europe. In addition, selective sweep signatures in P. armeniaca during domestication from wild to cultivated apricots, combined with differentially expressed genes, underlie distinct fruit traits, including sugars, aromas, organic acids, and carotenoids. This study provides substantive and valuable genomic resources that will significantly advance apricot improvement and effective utilization.